Laparoscopic Surgery for Adult Intussusception: Case Series - Yüksel, Adem; Coşkun, Murat (Turkish Journal of Gastroenterology, 2021)
Background/Aims: Intussusception is a rare condition in adults which accounts for 1% of all intestinal obstructions. It usually requires surgical treatment and the classic approach is laparotomy. This article presented six adult patients who underwent laparoscopic surgery for intestinal obstruction due to intussusception. Materials and Methods: Between January 2017 and July 2019, six adult patients underwent laparoscopic surgery for intestinal obstruction due to intussusception. The patients were evaluated in terms of presenting symptoms, diagnosis, treatment modality, morbidity, mortality and histopathological results. Results: All patients presented with acute (50%) or subacute (50%) symptoms. All patients had intestinal obstruction (partial, complete) findings. Intussusception was diagnosed by abdominal computed tomography (CT). The patients with ileocolic and colo-colonic intussusception underwent colonoscopy. In the preoperative period, the etiology of intussusception (neoplasm, idiopathic, etc.) was diagnosed only in one patient (16.6%). Two patients underwent laparoscopic segmental small bowel resection, two patients underwent laparoscopic right hemicolectomy, one patient underwent laparoscopic left hemicolectomy, and one patient underwent laparoscopic anterior resection. None of the patients developed intraoperative or postoperative complication. The histopathological examination revealed malignancy in two patients (33.3%). Conclusion: CT is helpful in diagnosing of adult intussusception. However, it is usually difficult to define the underlying pathology with CT. Laparoscopic approach seems to be safe and effective as open surgery, both in diagnosis and treatment of intussusception.